Role of gut microbiota against calcium oxalate. (August 2017) - Sadaf, Humaira; Raza, Syed Irfan; Hassan, Syed Waqas
Abstract: Nephrolithiasis is a condition marked by the presence or formation of stones in kidneys. Several factors contribute to kidney stones development such as environmental conditions, type of dietary intake, gender and gastrointestinal flora. Most of the kidney stones are composed of calcium phosphate and calcium oxalate, which enter in to the body through diet. Both sources of oxalates become dangerous when normal flora of gastrointestinal tract is disturbed. Oxalobacter and Lactobacillus species exist symbiotically in the human gut and prevent stone formation by altering some biochemical pathways through production of specific enzymes which help in the degradation of oxalate salts. Both Oxalobacter and Lactobacillus have potential probiotic characteristics for the prevention of kidney stone formation and this avenue should be further explored.